Peran Pelatihan dan Pengembangan dalam Meningkatkan Kinerja Dosen di Perguruan Tinggi - Suspahariati Suspahariati; Bambang Setyobudi (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2021)
Institutions and companies need improvement of work performance, so every institution or company will strive to support the effort of its employees. Universitas Pesantren Tinggi Darul Ulum (Unipdu) Jombang is an educational institution that also aims to improve work performance, especially the performance of lecturers. It is essential to provide a balanced impact to students and campus globally. Therefore, Unipdu conducts supportive activities by facilitating training and self-development for lecturers, both held locally by Unipdu and at the national level under The Ministry of Education, Culture, Research, and Technology (Kemdikbudristek). Based on these problems, the researcher analyses the role of research and self-development and its impact on lecturer performance by applying descriptive qualitative methods. This research reveals an improvement in lecturers’ performance at Unipdu after carrying out training and self-development activities. With the advancement of the quality of lecturer performance, there will be an improvement in the quality of more directive students, as evidenced by the lecturers’ delivery of lecture materials.